A Survey-Based Emission Inventory of Greenhouse Gases Released from Rice Production on Consolidated Land in the Red River Delta of Vietnam - Dinh Thi Hai Van; Nguyen Thi Kim Oanh; Nguyen Thi Bich Yen (Atmosphere, 2025)
In this study, relevant rice cultivation data were collected through a local survey, and the life cycle assessment (LCA) method was employed to quantify greenhouse gas (GHG) emissions from rice production on consolidated land in the Red River Delta (RRD). Systematic sampling was used in face-to-face interviews with 45 rice farming households in a representative commune of Hai Duong province. Specific GHG emissions were significantly higher in the summer crop (averaged at 11.4 t CO2-eq/ha or 2.2 t CO2-eq/t grain) than in the spring crop (6.8 t CO2-eq/ha or 1.2 t CO2-eq/t grain). Methane was a dominant GHG emitted from paddy fields, contributing 84% of the total emissions of CO2-eq in the summer crop and 73% in the spring crop. Fertilizer use and N2O emissions accounted for 9% of emissions in the summer crop and 16% in the spring crop. Energy consumption for machinery and irrigation added a further 4% and 8%, respectively. Annually, as of 2023, the rice production activities in the RRD release 7.3 Tg of CO2-eq (100 years), a significant contribution to the national GHG emissions. GHG emissions under alternative scenarios of rice straw management were assessed. This study highlights the role of land consolidation in improving water management, which contributes to lowering emissions. Based on the findings, several mitigation measures could be identified, including improved irrigation practices, optimized fertilizer use, and the promotion of sustainable rice straw management practices.